Zapomniana unia: reformy ustrojowoprawne w Szkocji w dobie angielskiej okupacji wojskowej (1651–1660) - Szymura, Mateusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The subject of this study is the analysis of the political and legal changes that were introduced by the occupying authorities of the English Republic after the defeat of royalist troops at the Battle of Dunbar on September 3, 1650. The initial period of political change amounted to the suspension of the Scottish Parliament and the judiciary deriving its mandate from royal authority. This period was associated with further military action, partisan battles and uprisings which lead predominantly to military administration of occupying forces under the command of general George Monck. The second period, which started in 1655, saw the gradual formation of bodies of a central administration—in the case of Scotland, this was the so-called Scottish Commission. The nature of this body’s subordination to its English counterpart, the fact that “Scottish” seats in the English Parliament were held mostly by Englishmen and the lack of knowledge of Scottish law among the English judges delegated to decide cases in Scotland meant that the union lacked even the appearance of equality between the two entities. Although the political experiment of the English Revolutionary period did not generally bring permanent reform, it was the first fitting for the foundation of the real union, which occurred half a century later in different form: monarchic rather than proposed republican one.
Keywords: Scotland; Commonwealth; Monck, George (1608-1670); judicial reform; Commission for the Administration of Justice; Charles II; Cromwell, Oliver (1599-1658); Scottish Commission